INDOOR PLAYGROUND UNTUK DEWASA SEBAGAI FASILITAS HEALING DI MAL: INDOOR PLAYGROUND FOR ADULTSAS A HEALING FACILITY IN MALL - Maya Dafina; Ariani; Awang Eka Novia Rizali; Woro Asty Werdina; Hendy Rosadi (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2025)
The intensity of urban stress experienced by adults in big cities, such as Jakarta, has led to the emergence of active recreational facilities that play a role in restoring physical and mental balance. Play activities have the potential to be a medium for healing, but until now, play areas in shopping centers are still dominated by concepts for children, making them less relevant for adult users. This study aims to examine the potential for developing indoor playgrounds for adults as active recreational facilities in malls. The method applied is a descriptive qualitative approach through literature study, direct observation of six playground facilities in the Jakarta-Tangerang area, and a survey of 57 adult respondents. The results show that the facilities are not suitable for adult needs, particularly in terms of privacy, safety, activity balance, and design approach. Based on these findings, this study formulates the concept of an Adult Interactive Play Lounge that integrates moderate physical activity, creative activities, social elements, and interactive technology to provide a holistic healing experience in an urban mall environment.